Factors associated with nonattendance at annual diabetes check-up in Ningbo, China: a case-control study - Li, Ling; Chattopadhyay, Kaushik; Li, Xueyu; Yu, Jingjia; Xu, Miao; Chen, Xueqin; Li, Li; Li, Jialin (Frontiers in Public Health, 2023)
Background Type 2 diabetes mellitus (T2DM) is a grave issue in China. The annual check-up is recommended in clinical guidelines on T2DM. It plays an important role in monitoring and managing the condition and detecting and managing any comorbidities and T2DM-related complications. However, people with T2DM may miss the annual check-up, and the benefits of this check-up are lost. Therefore, this study aimed to determine the factors associated with nonattendance at the annual T2DM check-up in Ningbo, China. Methods A case-control study was conducted using the Ningbo National Metabolic Management Center dataset. Cases were people with T2DM who were alive but did not attend the first annual check-up, scheduled between 1 March 2019 and 28 February 2022 (n = 1,549). Controls were people with T2DM who were alive and attended the first annual check-up during the same period (n = 1,354). The characteristics of cases and controls were compared using logistic regressions. Results The odds of being a female [odds ratio (OR) 1.26, 95% confidence interval (CI) 1.06–1.50], alcohol drinker (1.26, 1.06–1.49), and with glycated hemoglobin A1c (HbA1c) ≥7% (1.67, 1.42–1.97) were higher among case patients than controls. The odds of being a high school graduate (0.77, 0.66–0.89) and on standard treatments in addition to lifestyle modification (oral hypoglycemic drug 0.63, 0.42–0.96; oral hypoglycemic drug and injection therapy 0.48, 0.32–0.73) were lower among case patients than controls. Conclusion The factors associated with nonattendance at the annual T2DM check-up in Ningbo, China were female sex, not a high school graduate, alcohol drinker, HbA1c ≥7%, and only on lifestyle modification. The study findings should be used for improving attendance at the annual check-up among people with T2DM in Ningbo.